2017
DOI: 10.1242/bio.029991
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β42 peptide is toxic to non-neural cells inDrosophilayielding a characteristic metabolite profile and the effect can be suppressed by PI3K

Abstract: The human Aβ42 peptide is associated with Alzheimer's disease through its deleterious effects in neurons. Expressing the human peptide in adult Drosophila in a tissue- and time-controlled manner, we show that Aβ42 is also toxic in non-neural cells, neurosecretory and epithelial cell types in particular. This form of toxicity includes the aberrant signaling by Wingless morphogen leading to the eventual activation of Caspase 3. Preventing Caspase 3 activation by means of p53 keeps epithelial cells from eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In the other models, human AβPP is co‐expressed with human BACE1 allowing the production of C99 and different isoforms of the Aβ peptide (including post‐translationally modified Aβ variants) through the processing of human AβPP by human BACE1 and by endogenous fly γ‐secretase (the AβPP‐BACE1 fly model) . AD fly models have been frequently used during the last two decades to investigate Aβ toxicity, cell‐specific vulnerability and aggregation . However, potential differences in the toxic mechanisms between the two different AD fly models have not been thoroughly investigated.…”
mentioning
confidence: 99%
“…In the other models, human AβPP is co‐expressed with human BACE1 allowing the production of C99 and different isoforms of the Aβ peptide (including post‐translationally modified Aβ variants) through the processing of human AβPP by human BACE1 and by endogenous fly γ‐secretase (the AβPP‐BACE1 fly model) . AD fly models have been frequently used during the last two decades to investigate Aβ toxicity, cell‐specific vulnerability and aggregation . However, potential differences in the toxic mechanisms between the two different AD fly models have not been thoroughly investigated.…”
mentioning
confidence: 99%
“…At the same time, it was shown that the negative effects of Aβ are not tissue-specific. The expression of the human Aβ42 peptide in adult Drosophila in a tissue- and time-controlled manner revealed that Aβ42 is also toxic in different non-neural cell types, including neurosecretory and epithelial cells [ 39 ]. The toxic effect may be associated with the Aβ-induced oxidative stress [ 14 ], as was evidenced by an increase in the expression level of Prx5 .…”
Section: Discussionmentioning
confidence: 99%
“…Synapse-promoting actions of PI3K are age-independent, as their activation at different times along adulthood generates new, supernumerary and fully functional synapses (Martín-Peña et al, 2006;Acebes et al, 2011. Recently, we reported the protective activity of PI3K over the Aβ42 toxicity caused in nonneuronal cells (Arnés et al, 2017). Unraveling the mechanisms that underlie these protective effects of PI3K would be of potential therapeutic interest, in particular if the early onset of AD could be diagnosed.…”
Section: Introductionmentioning
confidence: 99%